MANAJEMEN KURIKULUM MERDEKA BELAJAR DALAM MENINGKATKAN MUTU PEMBELAJARAN EKONOMI DI SMA NEGERI 1 PURWAKARTA - Erawan, Raden Dewangga Tresna; Trianugrahwati, Desemberi; Ardiana, Lufi; Rostini, Deti; Mastiani, Emay (PENDIDIKAN SAINS DAN TEKNOLOGI, 2024)
One aspect that can be used to overcome learning quality problems is by updating the curriculum. Currently, the Ministry of Education of the Republic of Indonesia has initiated a new curriculum called the independent learning curriculum. This is also implemented at SMA Negeri 1 Purwakarta, a school that implements the Independent Learning Curriculum. The objectives to be achieved in this research are: (1) To determine the planning of the independent learning curriculum in improving the quality of learning economy at SMA Negeri 1 Purwakarta, (2) To determine the implementation of the independent learning curriculum in improving the quality of learning economy at SMA Negeri 1 Purwakarta, (3) To find out the evaluation of the independent learning curriculum in improving the quality of learning economy at SMA Negeri 1 Purwakarta. In this research, researchers used descriptive qualitative research. Meanwhile, the data analysis technique uses the Miles Huberman and Saldana model which includes data collection, data condensation and presentation and drawing conclusions. The results of this research are: (1) Planning for the independent learning curriculum at SMA Negeri 1 Purwakarta was carried out in June 2022 involving all stack holders. The procedure begins with preparing files, human resources and also facilities and infrastructure, then the planning results are uploaded to the page. The reference used is the Merdeka Mengajar Platform. (2) The procedure for implementing the independent learning curriculum has four stages, namely initial, developing, ready and proficient. The initial stage is the stage of composing the learning flow, the second stage is the developing stage, which is the stage of making adjustments to the learning flow, the third stage is the ready stage, which is the stage where the teacher arranges the learning flow according to the material and the fourth stage is the advanced stage, which is the stage of developing the learning flow in the learning process. In preparing learning, teaching modules are used and the strategies used in its application are knowledge obtained from training. Meanwhile, the learning model requires students to be active and independent. (3) Evaluation of the implementation of the independent learning curriculum is carried out using formative and summative evaluations. Formative evaluation is an evaluation carried out by assessing self-assessment while summative evaluation is carried out by giving assignments to students. Follow-up in the implementation of the independent learning curriculum is also highly expected. Development needs to be carried out so that the implementation of the independent learning curriculum can be carried out further.